Relationship between Attitude of Teachers to Mathematics and Teaching of Mathematics in Cape Coast Municipality - Kofi Davis, Ernest (Journal of Educational Development and Practice, 2008)
This study explored primary and junior secondary school (basic school) teachers' attitude toward mathematics, the teaching of mathematics and the relationship between the two. A survey of attitude of 190 basic schoolteachers from 22 basic schools in the Cape Coast municipality of Ghana was carried out using questionnaires. Data collected were analyzed using means and standard deviations. Pearson's correlation was used to investigate the relationship between teachers’ attitude toward mathematics and the teaching of mathematics. The results from the study revealed among others that teachers had positive attitude towards mathematics (M = 39 out of 50, sd = 8.0) and the teaching of mathematics (M = 71.7out of 90, sd = 9.9). The study also revealed a moderate correlation between teachers’ attitude toward mathematics and the teaching of mathematics